Technical Note: The Definition of New Dental Morphological Variants Related to Malocclusion - Marin A. Pilloud (Dental Anthropology Association, 2018)
Since the codification of the Arizona State University Dental Anthropology System over 25 years ago, few additional morphological traits have been defined. This work serves to expand the current suite of traits currently collected by biological anthropologists. These traits surround various issues of malocclusion and follow clinical definitions of these traits as well as incorporate observed population variation in character states. These traits include issues of spacing (i.e., diastema and crowding) as well as mandibular and maxillary occlusion (i.e., overbite, underbite). A discussion of the etiology and utility of these traits in bioarchaeological and forensic anthropological research is also given.